Uporaba programskih grafov pri ugotavljanju vzporednosti v računalniških algoritmih - Jerman-Blažič, Borka (Informatica (Ljubljana), 1984)
Techniques of program graph analysis are used to measure the parallelism in computer programs. For a given semantic model of arhitectural support, characteristic timing equations are first constructed from the high level program to describe the sequential and parallel execution times. The ratio of these equations is then used as a measure of the inherent parallelism in the program. Graph analysis techniques are illustrared using two data flow models of arhitecture support. The basic feature of data flow computers are described very briefly.
Keywords: analiza algoritmov; computer science; data flow; graph theory; matematika; parallelism in computer algorithms; pretok podatkov; program graph; programski graf; računalniške arhitekture; računalništvo; teorija grafov; vzporednost algoritmov